EFEKTIVITAS HYPNOTERAPI TEKNIK ANCHOR TERHADAP PERUBAHAN PERILAKU MEROKOK REMAJA Studi Pada Klien di Klinik Maulana Center of Hypnotherapy Palembang - Budiman Budiman (Psikis : Jurnal Psikologi Islami, 2016)
Adolescent smoking behavior is one of the behaviors that are formed through the influence of  the  environment  and  the  curiosity  of a  teenager  on  the  enjoyment  of  cigarettes  by  a  teenager. Smoking is also not only occurs in adolescent boys by the results of the study found  that smoking behavior  also  applies  to  young  women  as  well  as  children  who  are  still  in  primary  school.  This study  examines  the  effectiveness  Anchor  Techniques  of  Hypnoterapy  toward  Adolescent  Smoking Behavior Change. Study for Client in The Clinic Maulana Center of Hypnotherapy Palembang. The hypothesis  of  this  study  is  there  Effect  of  Anchor  Techniques  of  Hypnoterapy  smoke  Adolescent Behavior Change. Research for Clients in The Clinic Maulana Center of Hypnotherapy Palembang. This  study  included  a  quantitative  study  in  which  research  methods  used  was  Quasi  Experiment design with pretest and posttest with non-control group design, a design study aimed at testing the causal  relationship  (Polit  &  Beck,  2006).  This  study  will  be  conducted  at  the  Clinic  Maulana Center  of  Hypnotherapy  Palembang  on  March-June  2015.  The  Clinic  is  located  at  street  Kebun Bunga  complex  BNI  Block  B  4  Sukarami  Palembang  and  sampling  techniques  using  purposive sampling with 15 respondens and using t-test data analysis and MANOVA. The results of this study stated  that  there  Effect  Anchor  Techniues  of  Hypnotherapy toward  Adolescent  Smoking  Behavior Change. The changes meant is leading to better behavior and that, of 15 people treated with anchor techniques of hypnotherapy 11 people stop smoking while two people can reduce the intensity and frequency of smoking to 78% while the two others are only able to be able to reduce the intensity of smoking 56, 3%. It is advisable to adolescents to be more selective in choosing friends relations, peer  groups,  and  the  utilization  of  spare  time  with  positive  activities.  Trying  to  avoid  and  try smoking, improve self-control and self-regulation to the development of technology and information in order to avoid negative environment.